Fostering Commercialization of Innovation and Student Entrepreneurship in Innovation Ecosystems: the Case of the Business Center of North Savo in Finland (National Administration Journal, 2021)
The capability to plan and execute commercialization processes of innovation is crucial for entrepreneurs, SMEs and large companies in a dynamic business environment. Enterprising students particularly need Innovation Support Services (ISS) that focus on their needs, type of service and quality of delivery. Using the case study methodology, this research presents the initiative of the Business Center of the North Savo Program in Finland. Results indicate that entrepreneurs and small firms typically conduct similar steps and, therefore, it is essential to create a comprehensive blueprint of innovation services based on the needs and tailored to the respective phase of commercialization processes.
Keywords: Commercialization process; innovation support services; student entrepreneurship; Finland